2021
DOI: 10.21037/tcr-21-564
|View full text |Cite
|
Sign up to set email alerts
|

A fatal multiple-lesion, inflammatory, pseudotumor in the lung: a rare case report

Abstract: An inflammatory pseudotumor is considered a benign form of lesion marked by a proliferation of myofibroblasts with different degrees of inflammatory infiltrates. Pulmonary inflammatory pseudotumors (PIPs) are extremely rare in middle-aged adults. Normally, a PIP has a single lesion, and can be controlled constantly by surgery and drugs. In this paper, we report a case study of a 51-year-old male patient who presented with multiple inflammatory pseudotumors in lungs, thoracic spine, ribs, left humerusl, derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[ 29,30 ] Further studies have shown that vincamine acts as a brain metabolism booster by affecting peripheral vascular diastole, ATP production, and efficient use of glucose and oxygen to combat hypoxia and ischemia. [ 31 ] Vincamine can also improve neural protection by enhancing noradrenergic, serotonergic, and dopaminergic functions via its antioxidant capacity. [ 32 ] Existing clinical study has shown that vincamine effectively reduces vertigo and tinnitus in elderly patients with neuropsychiatric symptoms, suggesting its potential activity in improving cochlear functions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29,30 ] Further studies have shown that vincamine acts as a brain metabolism booster by affecting peripheral vascular diastole, ATP production, and efficient use of glucose and oxygen to combat hypoxia and ischemia. [ 31 ] Vincamine can also improve neural protection by enhancing noradrenergic, serotonergic, and dopaminergic functions via its antioxidant capacity. [ 32 ] Existing clinical study has shown that vincamine effectively reduces vertigo and tinnitus in elderly patients with neuropsychiatric symptoms, suggesting its potential activity in improving cochlear functions.…”
Section: Introductionmentioning
confidence: 99%